Estudos florísticos e fitossociológicos em comunidades vegetais de restinga da Ilha do Cardoso, Cananéia, SP - Sugiyama, Marie (2003)
The present study evolved floristic composition, structure and regeneration dynamic aspects of a restinga forest (pluvial sand coastal plain forest), at Ilha do Cardoso, in Cananéia region, São Paulo State, Brazil. Three portions of restinga forest with same physiognomic aspects were selected: restinga of Trilha para o Morro das Almas (MA), Trilha Interpretativa (TI) and Estrada para a Captação (EC). Five strata of forest were sampled in each portion: Tree, Tree/shrub, Shrub/herbaceous, Herbaceous and Lianas. Each portion was analyzed individually and subsequently were analyzed the entirely of the three portions and compared them. At Trilha para o Morro das Almas were sampled 73 species, at Trilha Interpretativa 72, at Estrada para a Captação 56 and totally sample 112, inside them 31 species were common to three portions and 46 restrict only one of them. The three portions of a forest were floristically similar, MA and TI had the highest Sørensen similarity (70,3%), and TI and EC had the less Sørensen similarity (55,5%). When compared the strata in general Tree/shrub and Shrub/herbaceous strata had the highest value of Sørensen similarity, and the Tree and Herbaceous strata had the less similarity. The highest diversity and equability were found in herbaceous strata, and the less in tree strata. The plants of the three portions had majority of species with geographic distribution in south and southeast Brazil regions, and the majority individuals and species were secondary-climax category. The portions of studied forest were in advanced stage of regeneration, and shade-tolerant species were favored. The differences between three portions of a forest were due to natural process common in tropical forests, where the substitution of one tree produce a mosaic of distinct regenerative phases at community that differ in structure and floristic composition. Differences in environment physical conditions, especially edaphic factors, and distinct anthropic interventions are responsible too.